# given expression b 4 ( 3 a b 3 ) ( 2 a 2 b − 5 ) .

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

#### Solutions

Chapter 1.2, Problem 42E

(a)

To determine

## To simplify: given expression b4(3ab3)(2a2b−5) .

Expert Solution

b4(3ab3)(2a2b5)=6a3b2

### Explanation of Solution

Given information:

Given expression

b4(3ab3)(2a2b5)

Calculation:

Consider the given expression.

b4(3ab3)(2a2b5)

And eliminate any negative exponents. To simplify this, first rewrite this expression as a single product.

b4(3ab3)(2a2b5)=32aa2b4b3b5=6aa2b4b3b5

Now, use the first law of exponents, which states

aman=am+n

And combine like terms

6aa2b4b3b5=6a1+2b4+35=6a3b2

Hence,

b4(3ab3)(2a2b5)=6a3b2

(b)

To determine

### To evaluate: the given expression (2s3t−2)(14s7t)(16t4) .

Expert Solution

(2s3t2)(14s7t)(16t4)=8s10t3

### Explanation of Solution

Given information:

Given expression

(2s3t2)(14s7t)(16t4)

Calculation:

Consider the given expression.

(2s3t2)(14s7t)(16t4)

And eliminate any negative exponents. To simplify this, first rewrite this expression as a single product.

(2s3t2)(14s7t)(16t4)=21416s3s7t2tt4=8s3s7t2tt4

Now, use the first law of exponents, which states

aman=am+n

And combine like terms

8s3s7t2tt4=8s3+7t2+1+4=8s10t3

Hence,

(2s3t2)(14s7t)(16t4)=8s10t3

### Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!